Multi-disciplinary innovation response to extraordinary pandemic - Ooi, Yasmin Beng Houi; Jurry Foo; Mansoor Abdul Hamid (UniSE Press, 2024)
Sabah’s fruit and vegetable farmers were saddled with stockpiles of their fresh produce during the movement restriction orders enforced as part of control to contain the spread of infection during the COVID-19 pandemic. This resulted in loss of their livelihood because their produce could not reach consumers beyond their district and the land border closure stopped exports to Sarawak and Brunei. Calls for assistance were placed in local social media groups and word-of-mouth. Universiti Malaysia Sabah researchers, in consultation with the farmer community, responded by transferring knowledge on food product innovations and other technological innovations to the farmers. The Diffusion of Innovation Theory was used to explain the successes and challenges encountered. Cabbage floss and tomato sauce innovations that had reached different levels of market are used as examples.